2021
DOI: 10.1093/eurheartj/ehab724.1713
|View full text |Cite
|
Sign up to set email alerts
|

Independent risk factors of mortality in streptococcal infective endocarditis

Abstract: Background Streptococcal bloodstream infection (BSI) is a common cause of infective endocarditis (IE), yet prognostic factors for mortality are poorly investigated. Purpose To investigate risk factors associated with in-hospital and one-year mortality in streptococcal IE. Methods All patients with a streptococcal BSI, from 2008 to 2017, were included in a reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Suh et al ( 23 ) reported that previous steroid use and immunosuppressant use were associated with increased mortality in viridans streptococcal IE. In a recent unpublished study, Chamat-Hedemand et al ( 24 ) reported that renal disease at the time of IE diagnosis was significantly associated with 1-year mortality in streptococcal IE, which is in line with our findings. However, although they reported that bovis group infection was associated with lower mortality, we could not identify the association between particular streptococcal species and mortality due to the limited sample size.…”
Section: Discussionsupporting
confidence: 92%
“…Suh et al ( 23 ) reported that previous steroid use and immunosuppressant use were associated with increased mortality in viridans streptococcal IE. In a recent unpublished study, Chamat-Hedemand et al ( 24 ) reported that renal disease at the time of IE diagnosis was significantly associated with 1-year mortality in streptococcal IE, which is in line with our findings. However, although they reported that bovis group infection was associated with lower mortality, we could not identify the association between particular streptococcal species and mortality due to the limited sample size.…”
Section: Discussionsupporting
confidence: 92%
“…This is notable as previously, Kingella spp. appeared to have the highest rate of CNS embolism of all HACEK organisms, with a rate of 20%–30%[ 55 ]. Embolic events have been associated with worse prognosis in IE, with the risk proportional to vegetation size > 10 mm[ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%